Rebalancing, Growth, and Development in a Multipolar Global Economy - Qureshi, Zia (World Bank, Washington, DC, 2012)
Reduction of large and persistent external imbalances is currently a key focus of G-20 discussions. The paper argues that in a progressively multipolar world economy, the goals of global rebalancing, growth, and development are increasingly inter-linked. Growth-oriented rebalancing calls for emphasizing structural reforms and leveraging the role of developing countries in supporting strong and balanced global growth.